Modifikasi Ovitrap dan Tingkat Partisipasi Masyarakat dalam Meningkatkan Angka Bebas Jentik dengan Menggunakan Biji Jarak (Ricinnus communis) di Kota Medan - Indra Chahaya; Novrial Novrial (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Modification of ovitrap by using abate has been proven to increase the rate of the free number of larvae (ABJ) up to 80 % but difficulty of obtaining abate. Kelurahan Baru Ladang Bambu District of Medan Tuntungan is one of the endemic villages in Medan City. In this area, many plants are found Ricinnus communis whose leaves are often used to treat colds for babies and children while many seeds are wasted scattered. Based on that the researcher by using jatropha seed as material for ovitrap modification in improving ABJ. This research is a quasi-experiment research with pre-test and post-test. The population is home and community in Kelurahan Baru Ladang Bambu, the sample is 90 houses for three treatments, ie without treatment, ovitrap treatment with abate powder and ovitrap treatment with jatropha seed powder, with dose each 5mg / 100 l water. Interviews were also conducted with the community to know the level of participation in using ovitrap modification. Based on the result of the research, it is known that the modification of ovitrap with jatropha seed (p = 0,001) is more effective than using abate powder to increase ABJ. The level of public participation in using ovitrap modification is still low, this is seen from the actions of people who use modification ovitrap 54.44%. While the level of knowledge in the com-munity has increased well (78.88%). Modification of ovitrap by using jatropha seeds can increase the ABJ, it is expected that the community can use this method to reduce the density of mosqui-toes considering the easily accessible seeds in this area. Therefore, further research is needed to determine the appropriate dose in the provision of safe and non-odor-free seeds.